2016
DOI: 10.1007/s11095-016-2010-5
|View full text |Cite
|
Sign up to set email alerts
|

Emodin-Loaded PLGA-TPGS Nanoparticles Combined with Heparin Sodium-Loaded PLGA-TPGS Nanoparticles to Enhance Chemotherapeutic Efficacy Against Liver Cancer

Abstract: The research suggests that the combination therapy system of EPTNs and HPTNs could be a new direction for liver cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…There were some reports indicating that rhubarb extracts induced apoptosis or inhibit migration of cancer cells ( 9 , 10 ). For example, emodin extracted from rhubarb root has anti-cancer effects in numerous cancers such as prostate, breast and cervical cancers ( 11 15 ). Chrysophanol was also reported for its anti-cancer role, showing that it inhibits viability of colon cancer cells through inhibition of the NF-κB-mediated signaling cascades ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…There were some reports indicating that rhubarb extracts induced apoptosis or inhibit migration of cancer cells ( 9 , 10 ). For example, emodin extracted from rhubarb root has anti-cancer effects in numerous cancers such as prostate, breast and cervical cancers ( 11 15 ). Chrysophanol was also reported for its anti-cancer role, showing that it inhibits viability of colon cancer cells through inhibition of the NF-κB-mediated signaling cascades ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have shown that emodin can inhibit tumour growth by inhibiting tumour cell proliferation and inducing apoptosis (14)(15)(16). Emodin can also synergize with various antitumour drugs to reduce tumour resistance (17). Aloe-emodin, reported as a potential anticancer agent, has a molecular structure similar to that of emodin.…”
Section: Discussionmentioning
confidence: 99%
“… Liu et al, 2016a combined heparin and emodin with a nano-molecular carrier polylactic-co-glycolic acid-D- α -tocopheryl polyethylene glycol 1,000 succinate (PLGA-TPGS) to form heparin-loaded PLGA-TPGS nanoparticles and emodin-loaded PLGA-TPGS nanoparticles, respectively. Moreover, the researchers found that the two synergistically promote apoptosis in vivo and in vitro , and inhibit tumor growth in vivo ( Liu et al, 2016a ; Liu et al, 2016b ). Dong et al distributed emodin in a new type of biomaterial N-acetylaminogalactosyl-poly (lactide-co-glycolide)-succinyl-D-a-tocopherol polyethylene glycol 1,000 succinate (GalNAc-PLGA-sTPGS) to form a new type of nanoparticle, EGTPN, and found that EGTPN in vitro induced HepG2 apoptosis more effectively than emodin alone (H. Dong et al, 2018 ).…”
Section: Active Ingredients Of Rhei Radix Et Rhizoma Used For Hcc Tre...mentioning
confidence: 99%